Analysis of Deep Foundation Pit Pile-Anchor Supporting System Based on FLAC3D. (16th August 2022) - Sun, Yongshuai; Li, Zhiming
Abstract : Relying on a deep foundation pit project in Beijing, using FLAC3D three-dimensional finite-difference software simulation combined with displacement monitoring data verification method, the deep foundation pit excavation and three-pile and two-anchor rod support system in anhydrous sand pebble stratum are systematically analyzed, and summed up the variation law of formation stress, internal force of soil nail, axial force of bolt, stress and displacement of pile in the process of excavation and support of deep foundation pit. The results show that during the excavation of the foundation pit, the maximum horizontal displacement of the sidewall is not at the top of the pile and the top of the slope but at a certain distance below the top of the pile. The axial force of the anchor rod is unevenly distributed along the length direction, the axial force of the free section is equal, the axial force of the anchoring section decreases in turn, and the prestress of the anchor rod spreads to the anchoring section after tensioning and locking. The soil-nailed wall is a passive force-bearing system, the force is small during the excavation and support process, and the axial force distribution along the length direction is large in the middle and small at the two ends. By analyzing the variation law of stress and deformation, the timeliness of the data in the construction process is improved, and an effective and reasonable case reference is provided for the informatization construction of simulated relevant working conditions.